INTERNALISASI PRINSIP - PRINSIP ISLAM TENTANG ETIKA KERJA DALAM PERLINDUNGAN HAK PEKERJA DAN PELAKSANAAN HAK ATAS PEKERJAAN - Irianti, Rini (LPPM Unisba, 2010)
Worker rights and the right to work are interesting topics to be discussed, especially in the manpower development context in Indonesia. Respect and guarantee on the worker rights is a part of fairness principles in labor law and such guarantee is very important for the continuity of a business. The fulfillment of the rights became the responsibility of the companies. However, the workers also have the obligation and responsibility as well. As an integral part of the company, workers have an obligation and social concerns on the sustainability of the company. In this case, internalization of Islamic principles should be considered in carrying out the duties. This principle should also be guidelines for workers in maintaining order and regularity. Based on the analysis, it can be concluded that the general accepted norms, decency norms, the legal norms and moral norms obtain in all life aspects,. These norms cannot be separated, each has relevance, and the law actually is the essence of positive moral norms, especially the empirical moral norms in the society.